DAYA SAING PENDIDIKAN: REVIEW ATAS PONDASI DAN IMPLEMENTASI KEBIJAKAN - Muslishudin * (Jurnal Forum Tarbiyah, 2010)
The competitiveness of the global community of education deals with the problems of humanity. For that reason the development of curriculum should consider the major issues that developed in the global world. The curriculum that may be developed is an â€œeclecticâ€ between humanistic approach, reconstruction of social and academic. Meanwhile, the learning approach can be implemented with â€œexperiental learningâ€. From the government side should be put through categorization of the school on formal education, therefore the competitiveness of national education will experience acceleration.